Development of an information system to test formalin content in salted fish with Java NetBeans - Dewi Anggraini Anggraini; Robby Mafirli; Stella Apfiasari; Endi Permata; Yus Rama Denny; Irvan Akram (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2026)
Salted fish, nowadays, most traders use dangerous preservatives; the preservative is Formalin. Traders use these chemicals because food becomes more durable, even though it will be consumed by humans. But because of a lack of public knowledge about foods that contain hazardous chemicals. Therefore, an automatic device based on an Arduino Uno R3 microcontroller is designed. This Arduino Uno R3 microcontroller-based system can test food practically and effectively, which shows quantitative results, because it does not take a long time to see the results. The TCS3200 color sensor is used to detect food samples containing Formalin mixed with Formalin Main Reagent according to the dose. Then the sensor will detect the color that changes after everything has reacted, and the buzzer alarm will sound when the positive result contains Formalin. The test results will be displayed on the 16x2 LCD screen and Java NetBeans application, where the output is in the form of detection of formalin or formalin-free. Preliminary data collection in this study was conducted using literature and observation. Data analysis techniques used are quantitative analysis and qualitative analysis. Based on the results of the study, the level of performance test data, Development of Formalin Content Test Equipment in Salted Fish Using TCS3200 Color Sensor Based on Arduino Microcontroller, obtained a score of 74 with the category "Very Feasible".